Sistem Perancangan Web Penjualan Material Bangunan Pada PT Bangun Tiara Teknik - Bani Siregar; Firstianty Wahyuhening Fibriany (Universitas Bina Sarana Informatika, 2019)
Web-based information systems technology is one of the media information that is efficient and effective in the dissemination of information that can be accessed by anyone, anytime, and anywhere. Currently, many companies are already making use of web-based information systems technology to help his efforts in promoting his company, to introduce its product, getting consumers more, making transactions faster and provide satisfying service for consumers. PT. Bangun Tiara Teknik is a company engaged in the field of building materials. Sales system that exists today of PT. Bangun Tiara Teknik is still done manually, where starting from the process of supply of goods, the ordering of merchandise, the deals, the creation of shipping documents, to reporting, so it takes a lot of time and in create a document and are still often goes wrong in terms of record keeping and input data by the sales section. The results of the design of this web-based information system is the best solution to solve the problem. Error logging orders can be minimized and reporting can be done appropriately. Therefore, the authors are interested in making the design of information system of sales with web-based at PT Bangun Tiara Teknik. With web-based computerized system allows the addition of a number of consumers to purchase the desired product, consumer satisfaction against the speed and accuracy of orders as well as reporting.